Metal surface wave-absorbing and corrosion-preventing integrated coating and preparation method thereof
By spin-coating the PANI-CFBN composite material arranged in a directionally arranged manner on the metal surface and the lotus-like cast film liquid constructed by modified TiO2 nanoparticles, the problem of the lack of anticorrosion performance of wave absorbing materials in extreme environments is solved, and the combination of efficient electromagnetic wave absorption and anticorrosion performance is achieved, and the concealment and protection ability of the material are improved.
Patent Information
- Application Number
- CN202510014925.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-06
AI Technical Summary
Existing absorbing materials lack anti-corrosion properties when used in extreme environments and are susceptible to erosion by salt spray, acid and alkali and other chemical substances, limiting their service life and application range.
The lotus-leafed PANI-CFBN@TiO2 casting film liquid constructed from directionally arranged PANI-CFBN composite materials and modified TiO2 nanoparticles is adhered to the metal surface by spin coating to form an integrated coating for wave absorption and corrosion protection.
It realizes the combination of efficient electromagnetic wave absorption and excellent anti-corrosion performance, improves the concealment and protection capabilities of the material, and has environmentally friendly and wide application potential.
Smart Images

Figure CN119823616A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of functional composite materials, and relates to an integrated coating with wave-absorbing and anti-corrosion functions on a metal surface and a preparation method thereof. Background Art
[0002] In the 21st century, the widespread use of electronic and microwave technologies has brought about the problem of electromagnetic radiation pollution, which poses a threat to human health and the normal operation of precision electronic equipment. Long-term exposure to electromagnetic wave environments may cause health problems and even induce cancer. In the military field, with the advancement of radar technology, traditional military equipment faces greater risks of electromagnetic detection and attack, so there is a growing demand for absorbing materials that can reduce the radar cross-section of military targets and improve concealment. However, existing absorbing materials often lack the necessary anti-corrosion properties when used outdoors or in extreme environments, and are easily corroded by chemicals such as salt spray, acids and alkalis, which limits their service life and scope of application.
[0003] It is difficult for traditional materials to have both microwave absorption and anti-corrosion properties. Boron nitride and polyaniline are increasingly being studied for their unique physical and chemical properties in the fields of microwave absorption and anti-corrosion. When these materials are used alone, their microwave absorption and anti-corrosion properties are difficult to meet high-performance requirements. Through surface modification or compounding with other materials, their microwave absorption and anti-corrosion effects can be significantly improved. However, since these materials are easy to agglomerate, the performance of the composite material is severely limited. Therefore, researching and developing a new functional composite material that has both high-efficiency electromagnetic wave absorption performance and excellent anti-corrosion performance is of great strategic significance for reducing electromagnetic pollution, protecting human health, and improving the concealment and protection capabilities of military equipment.
[0004] The Chinese patent "A silicon nitride-silicon carbide porous ceramic absorbing material and its preparation method" (application number: CN202111550760.6, authorization number: CN114262230B, announcement date: 2022-12-13) discloses a method for preparing a silicon nitride-silicon carbide porous ceramic absorbing material. The porous material allows electromagnetic waves to be reflected on the surface of the material, and more electromagnetic waves can enter the interior of the material and be absorbed and attenuated. However, there is a problem of a relatively single absorbing mechanism, and there is still much room for improvement in improving the absorbing performance.
[0005] The Chinese patent "Preparation method of TiO2-coated carbonyl iron modified anti-corrosion and wave-absorbing composite material and its application in anti-corrosion and wave-absorbing coating" (application number: CN202410641098.2, authorization number: CN118496703A, announcement date: 2024.08.16) discloses a preparation method of TiO2-coated carbonyl iron modified anti-corrosion and wave-absorbing composite material and its application in anti-corrosion and wave-absorbing coating. Carbonyl iron is coated with TiO2 to obtain CIP@TiO2 powder. The material has excellent wave-absorbing properties, but due to the coating structure, the dispersibility is limited, which limits the wave-absorbing and anti-corrosion properties of the coating.
[0006] The Chinese patent "A polyaniline nanocomposite material for anti-corrosion coatings and a preparation method thereof, a polyaniline composite anti-corrosion coating" (application number: CN202311674116.9, authorization number: CN117659758A, announcement date: 2024.03.08) discloses a polyaniline nanocomposite material for anti-corrosion coatings and a preparation method thereof. Polyaniline is in situ polymerized on graphene nanosheets to avoid material agglomeration and optimize the structure, but the material has a relatively single function.
[0007] The Chinese patent "A heat-resistant and anti-corrosion resin-based absorbing coating and its preparation method" (application number: CN202411177087.X, authorization number: CN119039821A, announcement date: 2024.11.29) discloses a heat-resistant and anti-corrosion resin-based absorbing coating and its preparation method. The absorber is mixed with the resin slurry to obtain an absorbing coating, which is sprayed on the surface of the substrate and cured to obtain a heat-resistant and anti-corrosion resin-based absorbing coating. The coating has good anti-corrosion and absorbing properties, but the material has a single absorbing mechanism and limited corrosion resistance, which limits the application of the coating.
[0008] The Chinese patent "A zinc oxide / titanium dioxide / titanium carbide composite absorbing material and its preparation method" (application number: CN202310252776.1, authorization number: CN116333683A, announcement date: 2023.06.27) discloses a zinc oxide / titanium dioxide / titanium carbide composite absorbing material and its preparation method. x The zinc oxide / titanium dioxide / titanium carbide composite absorber is obtained by reacting with Zn(CH3COO)2·2H2O in an autoclave and heat-treating in a tube furnace under an argon atmosphere. However, the cost of the material is too high and the output is limited. Summary of the invention
[0009] The purpose of the present invention is to provide a metal surface coating with integrated wave absorbing and anti-corrosion functions and a preparation method thereof, so as to solve the problem of applying electromagnetic wave absorption technology in extreme environments.
[0010] The present invention adopts two technical solutions:
[0011] The first aspect adopts an integrated coating with metal surface absorbing and anti-corrosion functions, including: a lotus leaf-shaped PANI-CFBN@TiO2 casting liquid formed by a directional arranged PANI-CFBN composite material and modified TiO2 nanoparticles, and the casting liquid is attached to the metal surface by spin coating.
[0012] The second aspect adopts a metal surface integrated coating with microwave absorption and anti-corrosion functions and a preparation method thereof, comprising the following steps:
[0013] Step 1: Preparation of porous BNNS
[0014] Boric acid and urea are dissolved in ultrapure water, heated and stirred, filtered and dried, and then dispersed in water. Phosphoric acid is added, stirred evenly, and dried and then calcined in a horizontal tube furnace to obtain porous BNNS.
[0015] Step 2: Magnetic modification of porous BNNS
[0016] The porous BNNS prepared in step 1 was dispersed in deionized water, Co(NO3)2·6H2O and FeSO4·7H2O were dispersed in a mixture of water and ethylene glycol (EG), mixed evenly, mixed with the porous BNNS aqueous solution and added with ammonia water to react, and dried to obtain CoFe2O4-BNNS (CFBN).
[0017] Step 3: Oriented alignment of PANI-CFBN composites
[0018] The CoFe2O4-BNNS obtained in step 2 was dispersed in deionized water, aniline and acidic solution were added, and after stirring evenly, ammonium sulfate (APS) mixed with acidic solution was added. A pulsed magnetic field coil was installed on the outside of the beaker, and the mixture was stirred in an ice bath for 12 h. After standing, the mixture was washed and vacuum dried to obtain polyaniline / boron nitride composite nanomaterials (PANI-CFBN).
[0019] Step 4: Preparation of modified TiO2 nanoparticles
[0020] TiO2 is added into a mixed solution of anhydrous ethanol and deionized water, and the pH value is adjusted with concentrated ammonia water; a coupling agent is added and stirred, aged at room temperature, and filtered and dried to obtain modified TiO2 nanoparticles.
[0021] Step 5: Construct lotus leaf-shaped PANI-CFBN@TiO2
[0022] The nanofillers prepared in step three and step four are dispersed in an organic solution, polyvinylidene fluoride (PVDF) powder is added, and the mixture is alternately stirred and ultrasonically treated. After standing, a uniform lotus leaf-shaped PANI-CFBN@TiO2 casting solution is obtained.
[0023] Step 6: Preparation of PVDF-based PANI-CFBN@TiO2 coating
[0024] The casting solution obtained in step five is spin-coated on the metal surface using a spin coater to form a coating, and then dried to obtain an integrated coating with microwave absorbing and anti-corrosion functions.
[0025] The present invention is also characterized in that:
[0026] In step 1, the molar ratio of uric acid to boric acid is 1:2-2:1, the storage temperature is 80-100°C, the time is 2-3h, the molar ratio of urea borate precursor to phosphoric acid is 1:1, the stirring time at room temperature is 8-12h, and the mixture is heated to 1100°C at a rate of 5°C / min in a horizontal tube furnace for 4-6h.
[0027] The amount of porous BNNS in step 2 is 0.01-0.02 mol, deionized water is 40-80 mL, the molar ratio of Co(NO3)2·6H2O and FeSO4·7H2O is 1:2, the volume ratio of the mixture of water and ethylene glycol (EG) is 1:3, the volume of the mixture is 40-80 mL, the ultrasonic stirring time is 30-60 min, the ammonia water is 4-6 mL, the high pressure reaction temperature is 180-200 ° C, and the reaction time is 24 h.
[0028] The acidic solution in step three is any one of hydrochloric acid solution and sulfuric acid solution, the concentration of the acidic solution is 1.5 mol / L, the concentration of aniline in the acidic solution is 0.006 g / mL to 0.012 g / mL, the concentration of CFBN in deionized water is 0.005 g / mL to 0.01 g / mL, and the volume ratio of deionized water to the acidic solution is 1:5. The stirring time is 4-6 hours, the concentration of APS in the acidic solution is 0.225 g / mL to 0.3 g / mL, and the mass ratio of APS to CFBN is 6:1 to 9:1. The pulse magnetic field coil is adjusted to a frequency of 50 Hz, the induction power is 2.2 kW to 12 kW, and the direction of the magnetic field is parallel to the bottom of the beaker.
[0029] In step 4, the volume ratio of anhydrous ethanol and deionized water is 1:1, the pH is adjusted to 9, the mass ratio of TiO2 and coupling agent (KH570) is 30:1-40:1, the concentration of TiO2 in the mixed solution of anhydrous ethanol and deionized water is 0.2 g / mL-0.3 g / mL, and the aging time at room temperature is 20-30 min.
[0030] The organic solution in step five is N-dimethylformamide (DMF), the mass ratio of PANI-CFBN, TiO2, and PVDF is 2:1:2-4:1:4, and the concentration of PANI-CFBN in DMF is 0.15 g / mL to 0.3 g / mL.
[0031] The drying temperature in step 6 is 120°C for 18-24 hours. The speed of the spin coater is set to 800-1000 rpm for 5 seconds, and the casting solution is 1.5-2 mL.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] A functional composite material with high efficiency in electromagnetic wave absorption and excellent anti-corrosion performance can be obtained. The porous boron nitride nanosheets are modified and polyaniline nanoparticles are grown on them to form an electromagnetic wave absorption layer, while providing additional interfaces to enhance absorption and scattering. The PANI-CFBN is arranged in a magnetic field to further optimize the structure and improve the dissipation capacity of electromagnetic waves. At the same time, the addition of TiO2 nanoparticles increases the dielectric constant of the material and improves the wave absorption capacity. The conductivity of polyaniline and the chemical stability of boron nitride jointly improve the anti-corrosion performance of the material. In addition, the addition of modified TiO2 nanoparticles constructs a unique lotus leaf-like microstructure and improves the hydrophobicity of the material. This material performs well in reducing electromagnetic pollution and improving military concealment. It is also environmentally friendly and has a wide range of application potential, indicating significant economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the microscopic morphology of the PVDF-based PANI-CFBN@TiO2 coating prepared by the present invention.
[0035] In the figure, 1-TiO2 nanoparticles, 2-polyaniline nanoparticles, 3-BNNS. DETAILED DESCRIPTION
[0036] The technical solution adopted by the present invention is a method for preparing an integrated material with wave absorbing and anti-corrosion functions, comprising the following steps:
[0037] Step 1: Preparation of porous BNNS
[0038] Urea and boric acid were dissolved in 100-200 ml ultrapure water at a molar ratio of 1:2-2:1, stored at 80-100°C for 2-3 hours, and filtered and dried after natural cooling to obtain a uric acid borate precursor (M·2B). Then, M·2B was dispersed in water, phosphoric acid was added at a molar ratio of 1:1 to M·2B, stirred at room temperature for 8-12 hours, and filtered and dried to obtain a white M·2B·P precursor. Next, the M·2B·P precursor was placed in a horizontal tube furnace, nitrogen was introduced, and heated to 1100°C at a rate of 5°C / min, and kept warm for 4-6 hours to obtain a loose porous BNNS.
[0039] Step 2: Magnetic modification of porous BNNS
[0040] 0.01-0.02 mol BNNS was dispersed in 40-80 mL water. At the same time, Co(NO3)2·6H2O and FeSO4·7H2O were dispersed in a mixture of 40-80 mL water and ethylene glycol (EG) (water:ethylene glycol volume ratio 1:3) at a molar ratio of 1:2, and ultrasonically stirred for 30-60 min to obtain solution A. The solution of dispersed porous BNNS was added to solution A, stirred evenly, and then 4-6 mL of ammonia water was added and stirred for 1-2 h, and reacted at high pressure of 180-200 ° C for 24 h. When the reaction was completed, the high-pressure steam was cooled to room temperature. The resulting precipitate was filtered, washed three times with deionized water and ethanol, and dried to obtain CoFe2O4-BNNS (CFBN).
[0041] Step 3: Oriented alignment of PANI-CFBN composites
[0042] Add aniline to a 1.5 mol / L acidic (hydrochloric acid, sulfuric acid) solution at a concentration of 0.006 g / mL to 0.012 g / mL and stir evenly. Add the CoFe2O4-BNNS obtained in step 2 to deionized water at a concentration of 0.005 g / mL to 0.01 g / mL, with a volume ratio of deionized water to acidic solution of 1:5. After ultrasonic dispersion, add it to the aniline mixture and stir for 4-6 hours. Add APS to an acidic (hydrochloric acid, sulfuric acid) solution at a concentration of 0.225 g / mL to 0.3 g / mL, with a mass ratio of APS to CFBN of 6:1 to 9:1. After stirring evenly, add it dropwise into the first solution, then install a pulse magnetic field coil on the outside of the beaker and adjust the frequency to 50 Hz, the induction power to 2.2 kW ~ 12 kW, the direction of the magnetic field is parallel to the bottom of the beaker, stir in an ice bath for 12 hours and then let it stand, wash with deionized water and ethanol 5 times each, and vacuum dry at 80 ° C for 24 hours to obtain polyaniline / boron nitride composite nanomaterials (PANI-CFBN).
[0043] Step 4: Preparation of modified TiO2 nanoparticles
[0044] Prepare a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:1, and adjust the pH to 9 with concentrated ammonia water; add TiO2 at a concentration of 0.2g / mL~0.3g / mL, ultrasonically disperse for 10 minutes, and stir at 80°C for 20 minutes; add KH-570, the mass ratio of TiO2 to coupling agent (KH570) is 30:1~40:1, stir for 1.5 hours, age at room temperature for 20-30 minutes, and filter and dry to obtain modified TiO2.
[0045] Step 5: Construct lotus leaf-shaped PANI-CFBN@TiO2
[0046] The nanofillers PANI-CFBN and modified TiO2 in steps three and four are added to the organic solution DMF, and a stable suspension is obtained after ultrasonic dispersion. Then, polyvinylidene fluoride (PVDF) powder is added to the suspension, wherein the mass ratio of PANI-CFBN, TiO2, and PVDF is 2:1:2-4:1:4, and the concentration of PANI-CFBN in DMF is 0.15 g / mL~0.3 g / mL. Magnetic stirring and ultrasonic treatment are used alternately, and then the mixture is allowed to stand to obtain a uniform lotus-shaped PANI-CFBN@TiO2 casting solution.
[0047] Step 6: Preparation of PVDF-based PANI-CFBN@TiO2 coating
[0048] The uniform casting solution is spin-coated on the metal surface using a spin coater, the coating speed is set to 800-1000 rpm, and the duration is 5-8 seconds. The casting solution is 1.5-2.0 mL. It is then dried at 120° C. for 18-24 hours to obtain an integrated coating with absorbing and anti-corrosion functions.
[0049] The present invention modifies the magnetic properties of porous boron nitride nanosheets, controls parameters to increase the electromagnetic wave magnetic loss mechanism, and enhances wave absorption. The modified porous BNNS loaded with polyaniline nanoparticles are oriented by controlling the magnetic field, so that the polyaniline has better conductivity in the doped state, can inhibit the corrosion process by electron transfer, and form a stable electromagnetic wave absorption layer, providing an additional interface to enhance absorption and scattering. TiO2 nanoparticles are modified by a coupling agent and coated on the surface of PANI-CFB N to construct a composite material with a lotus leaf-like microscopic morphology, thereby improving the hydrophobicity of the material. Boron nitride has excellent chemical stability, and can be combined with polyaniline and modified TiO2 to form a composite material with a synergistic effect, thereby optimizing the material's anti-corrosion performance and dielectric constant. The coating is prepared using PVDF as a matrix, and the interfacial bonding force of the coating is further enhanced by controlling the filler content.
[0050] The present invention modifies porous boron nitride nanosheets and grows polyaniline nanoparticles thereon to form an electromagnetic wave absorption layer, while providing an additional interface to enhance absorption and scattering. The PANI-CFBN is arranged in a magnetic field to further optimize the structure and improve the dissipation capacity of electromagnetic waves. At the same time, the addition of TiO2 nanoparticles improves the dielectric constant of the material and improves the wave absorption capacity. The electrical conductivity of polyaniline and the chemical stability of boron nitride jointly improve the anti-corrosion performance of the material. In addition, the addition of modified TiO2 nanoparticles constructs a unique lotus leaf-shaped microstructure and improves the hydrophobicity of the material. This material performs well in reducing electromagnetic pollution and improving military concealment, and is environmentally friendly and has a wide range of application potential, indicating significant economic and social benefits.
[0051] Example 1 Preparation of PVDF-based PANI-CFBN coating
[0052] First, urea (0.6 g) and boric acid (1.24 g) were dissolved in 200 ml ultrapure water, stored at 80 ° C for 2 h, naturally cooled to room temperature, filtered and dried to obtain urea borate precursor (M·2B). Then it was dispersed in water, 1 g of phosphoric acid was added, stirred at room temperature for 8 h, filtered and dried to obtain a white M·2B·P precursor. The M·2B·P precursor was placed in a horizontal tube furnace, nitrogen was introduced, and heated to 1100 ° C at a rate of 5 ° C / min, and kept warm for 4 h to obtain a loose porous BNNS.
[0053] 0.24g of porous BNNS was dispersed in 40mL of water. At the same time, 0.29g of Co(NO3)2·6H2O and 0.28g of FeSO4·7H2O were dispersed in a mixture of 40mL of water and ethylene glycol (EG) (water:ethylene glycol = 1:3), and stirred to obtain solution A. The solution of dispersed porous BNNS was added to solution A, stirred to obtain 4mL of ammonia water, stirred for 1h, and reacted at high pressure of 180℃ for 24h. When the reaction was completed, the high-pressure steam was cooled to room temperature. The obtained precipitate was filtered, washed with deionized water and ethanol 5 times, and dried at 60℃ to obtain CoFe2O4-BNNS.
[0054] Weigh 3g of aniline and add it to 500mL of 1.5mol / L sulfuric acid solution, and stir evenly. Weigh 1g of CoFe2O4-BNNS and add it to 100mL of deionized water, add it to the aniline mixture after ultrasonic dispersion and stir for 4h to obtain solution B, then add 6g of APS to another 20mL of 1mol / L sulfuric acid solution, stir evenly and add it dropwise to solution B, then install a pulse magnetic field coil outside the beaker to adjust the frequency to 50hz, the induction power to 2.2kw, the magnetic field direction is parallel to the bottom of the beaker, stir in an ice bath for 12h and then stand. Finally, the solution after standing was vacuum filtered, washed with deionized water and ethanol 5 times each, and vacuum dried at 80℃ for 24h to obtain polyaniline / boron nitride composite nanomaterials (PANI-CFBN).
[0055] Prepare 20 mL of a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:1, and adjust the pH to 9 with concentrated ammonia water; weigh 4 g of TiO2 and pour it into a beaker, ultrasonically disperse it for 10 minutes, and stir it at 80°C for 20 minutes; mix 0.2 g of KH-570 with 20 mL of ethanol and add it to the beaker, stir it for 1.5 hours, age it at room temperature for 20 minutes, and filter and dry it to obtain modified TiO2 particles.
[0056] Ultrasonic dispersion of 1g PANI-CFBN in 7ml DMF solution. Then add 1g polyvinylidene fluoride (PVDF) powder, stir evenly and let stand until there are no bubbles in the obtained composite colloid to obtain a uniform PANI-CFBN casting liquid. Then use a spin coater to spin coat the casting liquid on the metal surface. The spin coater speed is set to 800rpm for 5s. The casting liquid is 1.5mL, and then dried for 24h at a drying temperature of 120℃ to obtain an integrated coating with absorbing and anti-corrosion functions.
[0057] Example 2 Preparation of PVDF-based PANI-CFBN@TiO2 coating
[0058] First, urea (1.2 g) and boric acid (0.61 g) were dissolved in 200 ml ultrapure water, stored at 100 ° C for 2 h, naturally cooled to room temperature, filtered and dried to obtain urea borate precursor (M·2B). Then it was dispersed in water, 1 g of phosphoric acid was added, stirred at room temperature for 12 h, filtered and dried to obtain a white M·2B·P precursor. The M·2B·P precursor was placed in a horizontal tube furnace, nitrogen was introduced, and heated to 1100 ° C at a rate of 5 ° C / min, and kept warm for 6 h to obtain a loose porous BNNS.
[0059] 0.24g of porous BNNS was dispersed in 80mL of water. At the same time, 0.29g of Co(NO3)2·6H2O and 0.28g of FeSO4·7H2O were dispersed in a mixture of 40mL of water and ethylene glycol (EG) (water:ethylene glycol = 1:3), and stirred to obtain solution A. The solution of dispersed porous BNNS was added to solution A, stirred to obtain 6mL of ammonia water and stirred for 2h, and reacted at high pressure of 200℃ for 24h. When the reaction was completed, the high-pressure steam was cooled to room temperature. The obtained precipitate was filtered, washed with deionized water and ethanol 5 times, and dried at 60℃ to obtain CoFe2O4-BNNS.
[0060] Weigh 6g of aniline and add it to 500mL of 1.5mol / L sulfuric acid solution, and stir evenly. Weigh 0.5g of CoFe2O4-BNNS and add it to 100mL of deionized water, add it to the aniline mixture after ultrasonic dispersion and stir for 4h to obtain solution B, then add 4.5g of APS to another 20mL of 1mol / L hydrochloric acid solution, stir evenly and add it dropwise to solution B, stir in an ice bath for 12h and let it stand. Finally, the solution after standing was vacuum filtered, washed with deionized water and ethanol 5 times each, and vacuum dried at 80℃ for 24h to obtain polyaniline / boron nitride composite nanomaterials (PANI-CFBN).
[0061] Prepare 20 mL of a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:1, and adjust the pH to 9 with concentrated ammonia water; weigh 4 g of TiO2 and pour it into a beaker, ultrasonically disperse it for 10 minutes, and stir it at 80°C for 20 minutes; mix 0.1 g of KH-570 with 10 mL of ethanol and add it to the beaker, stir it for 1.5 hours, age it at room temperature for 30 minutes, and filter and dry it to obtain modified TiO2 particles.
[0062] 2g PANI-CFBN and 0.5g TiO2 were ultrasonically dispersed in 7ml DMF solution. Then 2g polyvinylidene fluoride (PVDF) powder was added, stirred evenly and allowed to stand until there were no bubbles in the obtained composite colloid to obtain a uniform PANI-CFBN casting solution. Then a spin coater was used to spin coat the casting solution on the metal surface. The spin coater speed was set to 800rpm for 5s. The casting solution was 1.5mL and then dried to obtain an integrated coating with absorbing and anti-corrosion functions.
[0063] Example 3 Preparation of PVDF-based PANI-CFBN@TiO2 coating
[0064] First, urea (0.6 g) and boric acid (1.24 g) were dissolved in 200 ml ultrapure water, stored at 80 ° C for 2 h, naturally cooled to room temperature, filtered and dried to obtain urea borate precursor (M·2B). Then it was dispersed in water, 1 g of phosphoric acid was added, stirred at room temperature for 12 h, filtered and dried to obtain a white M·2B·P precursor. The M·2B·P precursor was placed in a horizontal tube furnace, nitrogen was introduced, and heated to 1100 ° C at a rate of 5 ° C / min, and kept warm for 4 h to obtain a loose porous BNNS.
[0065] 0.48g of porous BNNS was dispersed in 80mL of water. At the same time, 0.29g of Co(NO3)2·6H2O and 0.28g of FeSO4·7H2O were dispersed in a mixture of 80mL of water and ethylene glycol (EG) (water:ethylene glycol = 1:3), and stirred to obtain solution A. The solution of dispersed porous BNNS was added to solution A, stirred to obtain 4mL of ammonia water, stirred for 2h, and reacted at high pressure of 180℃ for 24h. When the reaction was completed, the high-pressure steam was cooled to room temperature. The obtained precipitate was filtered, washed with deionized water and ethanol 5 times, and dried at 90℃ to obtain CoFe2O4-BNNS.
[0066] Weigh 3g of aniline and add it to 500mL of 1.5mol / L sulfuric acid solution, and stir evenly. Weigh 0.5g of CoFe2O4-BNNS and add it to 100mL of deionized water, add it to the aniline mixture after ultrasonic dispersion and stir for 6h to obtain solution B, then add 4.5g of APS to another 20mL of 1mol / L sulfuric acid solution, stir evenly and add it dropwise to solution B, then install a pulse magnetic field coil outside the beaker to adjust the frequency to 50hz, the induction power to 12kw, the magnetic field direction is parallel to the bottom of the beaker, stir in an ice bath for 12h and then stand. Finally, the solution after standing was vacuum filtered, washed with deionized water and ethanol 5 times each, and vacuum dried at 80℃ for 24h to obtain polyaniline / boron nitride composite nanomaterials (PANI-CFBN).
[0067] Prepare 20 mL of a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:1, and adjust the pH to 9 with concentrated ammonia water; weigh 6 g of TiO2 and pour it into a beaker, ultrasonically disperse it for 10 minutes, and stir it at 80°C for 20 minutes; mix 0.1 g of KH-570 with 10 mL of ethanol and add it to the beaker, stir it for 1.5 hours, age it at room temperature for 30 minutes, and filter and dry it to obtain modified TiO2 particles.
[0068] 1g PANI-CFBN and 0.5g TiO2 were ultrasonically dispersed in 7ml DMF solution. Then 1g polyvinylidene fluoride (PVDF) powder was added, stirred evenly and allowed to stand until there were no bubbles in the obtained composite colloid to obtain a uniform PANI-CFBN casting liquid. Then a spin coater was used to spin coat the casting liquid on the metal surface. The spin coater speed was set to 800rpm for 8s. The casting liquid was 2mL, and then dried to obtain an integrated coating with absorbing and anti-corrosion functions.
[0069] Example 4 Preparation of PVDF-based PANI-CFBN@TiO2 coating
[0070] First, urea (0.6 g) and boric acid (1.24 g) were dissolved in 200 ml ultrapure water, stored at 80 ° C for 2 h, naturally cooled to room temperature, filtered and dried to obtain urea borate precursor (M·2B). Then it was dispersed in water, 1 g of phosphoric acid was added, stirred at room temperature for 12 h, filtered and dried to obtain a white M·2B·P precursor. The M·2B·P precursor was placed in a horizontal tube furnace, nitrogen was introduced, and heated to 1100 ° C at a rate of 5 ° C / min, and kept warm for 4 h to obtain a loose porous BNNS.
[0071] 0.24g of porous BNNS was dispersed in 40mL of water. At the same time, 0.29g of Co(NO3)2·6H2O and 0.28g of FeSO4·7H2O were dispersed in a mixture of 80mL of water and ethylene glycol (EG) (water:ethylene glycol = 1:3), and stirred to obtain solution A. The solution of dispersed porous BNNS was added to solution A, stirred to obtain 4mL of ammonia water, stirred for 2h, and reacted at high pressure of 180℃ for 24h. When the reaction was completed, the high-pressure steam was cooled to room temperature. The obtained precipitate was filtered, washed with deionized water and ethanol 5 times, and dried at 60℃ to obtain CoFe2O4-BNNS.
[0072] Weigh 3g of aniline and add it to 500mL of 1.5mol / L sulfuric acid solution, and stir evenly. Weigh 0.5g of CoFe2O4-BNNS and add it to 100mL of deionized water, add it to the aniline mixture after ultrasonic dispersion and stir for 6h to obtain solution B, then add 4.5g of APS to another 20mL of 1mol / L sulfuric acid solution, stir evenly and add it dropwise to solution B, then install a pulse magnetic field coil outside the beaker to adjust the frequency to 50hz, the induction power to 12kw, the magnetic field direction is parallel to the bottom of the beaker, stir in an ice bath for 12h and then stand. Finally, the solution after standing was vacuum filtered, washed with deionized water and ethanol 5 times each, and vacuum dried at 80℃ for 24h to obtain polyaniline / boron nitride composite nanomaterials (PANI-CFBN).
[0073] Prepare 20 mL of a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:1, and adjust the pH to 9 with concentrated ammonia water; weigh 4 g of TiO2 and pour it into a beaker, ultrasonically disperse it for 10 minutes, and stir it at 80°C for 20 minutes; mix 0.1 g of KH-570 with 10 mL of ethanol and add it to the beaker, stir it for 1.5 hours, age it at room temperature for 20 minutes, and filter and dry it to obtain modified TiO2 particles.
[0074] 2g PANI-CFBN and 0.5g TiO2 were ultrasonically dispersed in 7ml DMF solution. Then 2g polyvinylidene fluoride (PVDF) powder was added, stirred evenly and allowed to stand until there were no bubbles in the obtained composite colloid to obtain a uniform PANI-CFBN casting solution. Then a spin coater was used to spin coat the casting solution on the metal surface. The spin coater speed was set to 800rpm for 5s. The casting solution was 2mL, and then dried to obtain an integrated coating with absorbing and anti-corrosion functions.
[0075] Comparative Example 1
[0076] The only difference from Example 4 is that no TiO2 nanoparticles are added in step 4.
[0077] Comparative Example 2
[0078] The only difference from Example 4 is that no magnetic field is introduced in step three.
[0079] Comparative Example 3
[0080] The only difference from Example 4 is that the mass ratio of PANI-CFBN to TiO2 is changed.
[0081] Table 1 is a comparison of the wave absorption and super hydrophobic performance of the coating with lotus leaf-like micro-morphology in Example 4, the coating of Comparative Example 1, the coating of Comparative Example 2 and the coating of Comparative Example 3. As can be seen from Table 1, the coating in Example 4 has the best comprehensive performance. The coating of Comparative Example 1 does not add TiO2 nanoparticles, which seriously affects the construction of a micro-nano structure with a lotus leaf shape. Comparative Example 2 does not introduce a magnetic field, the PANI-CFBN composite material agglomerates, the material structure is disordered, and the electromagnetic wave propagation path becomes shorter, which significantly affects the wave absorption performance of the material. Comparative Example 3 changes the mass ratio of PANI-CFBN to TiO2, and the TiO2 nanoparticles agglomerate seriously. In Example 4, the coating with a lotus leaf-like microstructure introduces a magnetic field to optimize the material structure. The porous BNNS extends the propagation path of electromagnetic waves and promotes the absorption and scattering of electromagnetic waves. The directional arrangement of polyaniline and modified porous boron nitride further improves the material's anti-corrosion and wave-absorbing properties. The addition of TiO2 nanoparticles constructs a unique lotus leaf-like microstructure, which significantly improves the material's superhydrophobic properties. Therefore, it has the best overall performance, which is better than all comparative examples.
[0082] Table 1 Comparison of the microwave absorption and anticorrosion performance of the PVDF-based PANI-CFBN@TiO2 coating in Example 4, the coating of Example 1, the coating of Example 2 and the coating of Example 3
[0083]
[0084]
[0085] Figure 1 Schematic diagram of the microscopic morphology of the PVDF-based PANI-CFBN@TiO2 coating prepared by the present invention. Figure 1 It can be seen that TiO2 nanoparticles are uniformly attached to the surface of PANI-CFBN.
[0086] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A metal surface coating with integrated microwave absorption and anti-corrosion functions, comprising: A lotus leaf-shaped PANI-CFBN@TiO2 casting solution is constructed by directional arrangement of PANI-CFBN composite materials and modified TiO2 nanoparticles, and the casting solution is attached to a metal surface by spin coating.
2. A method for preparing a metal surface coating with integrated microwave absorption and anti-corrosion functions, comprising the following steps: Step 1: Preparation of porous BNNS Boric acid and urea are dissolved in ultrapure water, heated and stirred, filtered and dried, dispersed in water, phosphoric acid is added, stirred evenly, dried, and calcined in a horizontal tube furnace to obtain porous BNNS; Step 2: Magnetic modification of porous BNNS The porous BNNS prepared in step 1 is dispersed in deionized water, Co(NO3)2·6H2O and FeSO4·7H2O are dispersed in a mixture of water and ethylene glycol, mixed evenly, mixed with the porous BNNS aqueous solution, and ammonia water is added to react, and dried to obtain CoFe2O4-BNNS; Step 3: Oriented alignment of PANI-CFBN composites The CoFe2O4-BNNS obtained in step 2 is dispersed in deionized water, aniline and acid solution are added, ammonium sulfate is added after stirring evenly, a pulse magnetic field coil is installed outside the beaker, ice bath is stirred, vacuum filtration, washing and drying are performed to obtain polyaniline / boron nitride composite nanomaterials; Step 4: Preparation of modified TiO2 nanoparticles TiO2 is added to a mixed solution of anhydrous ethanol and deionized water, and concentrated ammonia water is used to adjust the pH value; the coupling agent and ethanol are mixed and added, stirred, aged at room temperature, and filtered and dried to obtain modified TiO2 nanoparticles; Step 5: Constructing lotus leaf-shaped PANI-CFBN@TiO The nanofillers prepared in step 3 and step 4 are dispersed in an organic solution, polyvinylidene fluoride powder is added, and the mixture is stirred and ultrasonically treated alternately, and a uniform lotus leaf-shaped PANI-CFBN@TiO2 casting solution is obtained after standing. Step 6: Preparation of PVDF-based PANI-CFBN@TiO2 coating The casting solution obtained in step five is spin-coated on the metal surface using a spin coater to form a coating, and then dried to obtain an integrated coating with microwave absorbing and anti-corrosion functions.
3. The preparation method according to claim 2, characterized in that: In the step 1, the molar ratio of uric acid to boric acid is 1:2-2:1, and the molar ratio of urea borate precursor to phosphoric acid is 1:
1.
4. The preparation method according to claim 2, characterized in that: The horizontal tube furnace calcination in step 1 is heated to 1100° C. at a rate of 5° C. / min, and the heating time is 4-6 hours.
5. The preparation method according to claim 2, characterized in that: In the step 2, the amount of the porous BNNS substance is 0.01-0.02 mol, deionized water is 40-80 mL, the molar ratio of Co(NO3)2·6H2O and FeSO4·7H2O is 1:2, and the volume ratio of the mixture of water and ethylene glycol is 1:
3.
6. The preparation method according to claim 2, characterized in that: In step 3, the concentration of aniline in the acidic solution is 0.006 g / mL to 0.012 g / mL, the concentration of CFBN in deionized water is 0.005 g / mL to 0.01 g / mL, the volume ratio of deionized water to the acidic solution is 1:5, the concentration of APS in the acidic solution is 0.225 g / mL to 0.3 g / mL, and the mass ratio of APS to CFBN is 6:1 to 9:
1.
7. The preparation method according to claim 2, characterized in that: In step 3, the frequency of the pulse magnetic field coil is adjusted to 50 Hz, the induction power is 2.2 kW to 12 kW, and the direction of the magnetic field is parallel to the bottom of the beaker.
8. The preparation method according to claim 2, characterized in that: In step 4, the volume ratio of anhydrous ethanol and deionized water is 1:1, the pH is adjusted to 9, the mass ratio of TiO2 to coupling agent is 30:1-40:1, and the concentration of TiO2 in the mixed solution of anhydrous ethanol and deionized water is 0.2 g / mL-0.3 g / mL.
9. The preparation method according to claim 2, characterized in that: The organic solution in step five is N-dimethylformamide, the mass ratio of PANI-CFBN, TiO2, and PVDF is 2:1:2-4:1:4, and the concentration of PANI-CFBN in DMF is 0.15 g / mL to 0.3 g / mL.
10. The preparation method according to claim 2, characterized in that: The spin coater speed in step six is set to 800-1000 rpm for 5-8 s, and the casting liquid is 1.5-2.0 mL.
Citation Information
Patent Citations
Perpendicularly oriented boron nitride and organosilicone composite heat conductive thin film material under magnetic field and preparation method thereof
CN109181312A
Preparation method of BN fiber-based porous ceramic with multilayer structure
CN117645499A
Wave-absorbing heat-conducting super-hydrophobic anticorrosive coating and preparation method thereof
CN119242146A